Understanding the Relationship between Work Engagement and Job Satisfaction in Retail Workplaces - Aesa Aesa; Olievia Prabandini Mulyana (Al-Qalam Institue, 2026)
The retail industry is characterized by high work demands, including sales targets, intensive customer interactions, and dynamic operational conditions that may affect employees’ psychological well-being, particularly job satisfaction. This study aimed to examine the effect of work engagement on job satisfaction among retail employees. A quantitative approach with a correlational survey design was employed, involving 81 retail employees selected through purposive sampling. Work engagement was measured using the Utrecht Work Engagement Scale (UWES), while job satisfaction was assessed using the Job Satisfaction Survey (JSS). Data were analyzed using simple linear regression. The findings revealed that work engagement had a positive and significant effect on job satisfaction (R = 0.550; R² = 0.302; p < 0.001), indicating that employees with higher levels of vigor, dedication, and absorption tended to report greater job satisfaction. Work engagement contributed 30.2% to the variance in job satisfaction, suggesting a meaningful role in shaping employees’ positive evaluations of their work despite the demanding nature of the retail environment. These findings imply that organizations should strengthen employee engagement through supportive work environments, balanced workloads, meaningful work experiences, and employee development initiatives to enhance both employee well-being and organizational performance.